A single-centred retrospective observational analysis on mortality trends during the COVID-19 pandemic - Omishka Hirachund; Camilla Pennefather; Mergan Naidoo (South African Family Practice)
Background: South Africa experienced high mortality during the COVID-19 pandemic. Resources were limited, particularly at the district hospital (DH) level. Overwhelmed healthcare facilities and a lack of research at a primary care level made the management of patients with COVID-19 challenging. The objective of this study was to describe the in-hospital mortality trends among individuals with COVID-19 at a DH in South Africa.